Application of unified IP address management technologies in large-scale IPv4/IPv6 transition environment - Zi-mu LI; Yi-qi FU; Li PAN (Tongxin xuebao)
Some basic requirements of IP address management (IPAM) in large-scale IPv4/IPv6 transition environment in campus wired LAN and WLAN is summarized,and analyzes some special technologies of IPv6 address management as well as some operating key technologies of IPAM service in such environment.Finally,a real deployment of IPAM service in such a large-scale IPv4/IPv6 transition environment is introduced.Experience of unified IPAM service oriented next-generation wired LAN and WLAN are gathered.